Riders of the purple sage - Grey, Zane, 1872-1939 (Grey, Zane, 1872-1939. Riders of the purple sage., 1994)
Jane, a wealthy rancher living in a Mormon village, must marry the arrogant Elder Tull as the Mormon churchmen decree. But Lassiter rides into town to teach Tull and his mob a lesson.